Development of an Interactive Game Application using Linear Congruent Method (LCM) to Improve Hijaiyah Letter Recognition Skills in Children - Elistatia, Usi; Permatasari, Sisca (Gameology and Multimedia Expert, 2025)
Introducing Hijaiyah letters is an essential first step in early childhood education. To make learning these letters enjoyable, we developed an interactive game application using the Scratch platform. This application aims to help children recognize and memorize Hijaiyah letters in an engaging way. The development methodology employed is the Game Development Life Cycle (GDLC). We built the application by utilizing various features of Scratch, including animations, sounds, and user interactions. Users are invited to play while learning the Hijaiyah letters. After understanding the letters, they enter a game page where they must navigate toward the provided Hijaiyah letters. To avoid repeated appearances of the same letters, we applied the Linear Congruent Method (LCM) algorithm as a randomization technique. The LCM algorithm generates random numbers to shuffle the appearance of Hijaiyah letters in the game. Testing results show that using Scratch to develop this Hijaiyah letter recognition game is effective and can improve children's ability to recognize these letters.